Analisis Keabsahan Perjanjian Pengikatan Jual Beli Tanah yang Dibuat di Bawah Tangan Menurut KUHPerdata - Bintang Rahmawati; Suparwi Suparwi; Firstnandiar Glica Aini Suniaprily (Jurnal Hukum Lex Generalis, 2025)
Before land ownership is transferred through an authentic deed legalized before a Land Deed Official (PPAT), a sales and purchase agreement (PPJB) is often used as the initial agreement. In reality, PPJBs are often made privately rather than before a PPAT or notary. This raises legal questions regarding the validity and legal protection of the parties in disputes. The purpose of this study is to determine the validity of PPJBs made privately based on Articles 1320 and 1338 of the Civil Code concerning the requirements for a valid agreement, as well as the principles of freedom of contract and the binding force of the agreement. In addition, this study also discusses the legal implications of privately made land sale and purchase agreements on the protection of the parties' rights. This study uses a normative juridical method, where the research focuses on the study of positive law as stipulated in legislation, doctrine, and court decisions relating to the validity of PPJBs for private land.